2020
DOI: 10.1101/2020.02.17.949347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assortative mating and within-spouse pair comparisons

Abstract: Comparisons between cohabitating spouses have been proposed as an aetiological design method to reduce confounding and evaluate effects of the shared adulthood environment. However, assortative mating, a phenomenon where individuals select phenotypically similar mates, could distort associations. We evaluated the use of spousal comparisons, as in the within-spouse pair (WSP) model, for aetiological epidemiological research.Using directed acyclic graphs and simulations, we demonstrated that the WSP model can re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Additionally, the mean ages of the spouses in both studies were 57 and 63 years old, and so the findings regarding the correlation in sleeping patterns and circadian preferences between spouses may not necessarily extrapolate to younger couples, particularly those with contrasting work schedules. Furthermore, factors influencing selection into the UK Biobank and 23andMe (42), and spousal assortment on other traits (19), may bias spousal comparisons in both observational and MR analysis. However, previous simulations have suggested that this most likely results in bias towards the null, leading to an under-estimate of the true effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the mean ages of the spouses in both studies were 57 and 63 years old, and so the findings regarding the correlation in sleeping patterns and circadian preferences between spouses may not necessarily extrapolate to younger couples, particularly those with contrasting work schedules. Furthermore, factors influencing selection into the UK Biobank and 23andMe (42), and spousal assortment on other traits (19), may bias spousal comparisons in both observational and MR analysis. However, previous simulations have suggested that this most likely results in bias towards the null, leading to an under-estimate of the true effect.…”
Section: Discussionmentioning
confidence: 99%
“…Spousal concordance is well established in humans for several characteristics (14), including cardiometabolic health (15), smoking (15), alcohol consumption (16), educational level (17), language and culture (18). Spouses tend to be positively correlated for most measures phenotypes, and this may represent positive assortative mating or social homogamy (whereby individuals select phenotypically similar partners), interactions after partnership (where an individual's behaviour influences that of their spouse) which may result in convergence over time, or confounding by shared environmental factors (19). It is plausible that sleep traits between spouses may also be influenced by these processes.…”
Section: Introductionmentioning
confidence: 99%